Hedge and Alder-Based Agroforestry Systems: Potential Interventions to Carbon Sequestration and Better Crop Productivity in Indian Sub-Himalayas - Parmar, Brajendra; Vishwakarma, Anand; Padbhushan, Rajeev; Kumar, Amarendra; Kumar, Rajkishore; Kumari, Ragini; Kumar Yadav, Brahmdeo; Giri, S. P.; Kaviraj, Megha; Kumar, Upendra (Frontiers in Environmental Science, 2022)
Agroforestry systems (AFS) have the potential to combat climate change as well as to ensure food security. AFS can sequester carbon and amend the organic matter pools thereby enhancing crop productivity. Carbon sequestration depends on the type of AFS, climate, cropping pattern, and management practices. The aim of this study was to evaluate different AFS for their potential to sequester carbon and impact on soil organic matter in the eastern sub-Himalayas, India. Hedge, alder, and guava-based AFS were established along with control (without any tree) and maize-mustard-potato cropping pattern had been followed in each AFS. Soil samples were collected after the fifth crop cycle and further analyzed. The results showed that crop productivity was significantly higher in all the AFS than in the control. On average, soil organic carbon (SOC) was found significantly higher by 62% and 64% in hedge-based AFS as compared to guava-based AFS and control, respectively, and at par with alder-based AFS. Particulate organic carbon (POC) was more in all the three AFS over the control. Microbial biomass carbon (MBC) and nitrogen (MBN) content, the trend of AFS was as alder-based AFS>hedge-based AFS> guava-based AFS> control. Hedge-based and alder-based AFS had more SOC stocks than guava-based AFS and control. SOC stocks were more in the subsurface layer (10-20 cm) than surface layer in hedge-based and alder-based AFS while contrary to that in guava-based AFS and control, the SOC stocks were greater in soil depth 0-10 cm than soil depths 10-20 cm and 20-30 cm. Carbon dioxide (CO2) equivalent emissions were greater under control over hedge-based AFS (35.2 Mg ha-1) followed by alder-based AFS (28.6 Mg ha-1) and the lowest was observed under guava-based AFS. On average, hedges species accumulated more nitrogen, phosphorus, and potassium which were 60, 12, and 28 kg ha-1 yr-1, respectively. This conclusively proved that AFS are significantly affecting soil organic matter pools and crop productivity and had significant role in carbon retention in the soil. Hedge-based and alder-based AFS retained better soil carbon and hence, recommended for inclusion in climate-smart agriculture practices in climate-change mitigating strategy and ensures food security in Indian sub-Himalayas.